2020
DOI: 10.1017/xps.2020.33
|View full text |Cite
|
Sign up to set email alerts
|

Race, Dehumanization, and the NFL National Anthem Protests

Abstract: Dehumanizing language, or language used to describe human beings as non-human entities, is increasingly prevalent in political life. This dehumanization also occurs frequently in the world of sports. Sports and politics intersected notably in 2016, when Colin Kaepernick of the NFL’s San Francisco 49ers started protesting the national anthem to raise awareness about police violence against African-Americans. Kaepernick’s protests generated considerable vitriol towards him and other protesters, some of which was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 46 publications
1
7
0
Order By: Relevance
“…While the effects of dehumanization on attitudes are small, this is in line with other studies using language manipulations to study dehumanization (Utych, 2018;Utych, 2020). Other factors certainly influence attitudes toward terrorists more than dehumanizing language, but there is a small effect, even on a group that is nearly universally loathed.…”
Section: Dehumanization Treatmentsupporting
confidence: 85%
“…While the effects of dehumanization on attitudes are small, this is in line with other studies using language manipulations to study dehumanization (Utych, 2018;Utych, 2020). Other factors certainly influence attitudes toward terrorists more than dehumanizing language, but there is a small effect, even on a group that is nearly universally loathed.…”
Section: Dehumanization Treatmentsupporting
confidence: 85%
“…While this research shows how dehumanization can influence evaluations of employees on a broad, nationally diverse sample, it is not limited to only public managers. While we do not necessarily have reason to believe that public managers would react differently to dehumanizing rhetoric than Americans in general (see Utych, 2020 for a discussion of the lack of individual-level moderating effects of dehumanizing language on attitudes), further research would have to adjudicate this claim. Research on dehumanization has long suggested, however, that dehumanization is dependent much more on the context of who is dehumanized, rather than who is exposed to the dehumanization (Haslam, 2006).…”
Section: Discussionmentioning
confidence: 96%
“…The consequences of dehumanization are clear—when individuals, or groups in society, are dehumanized, this can be used as a justification for negative attitudes toward the group, or even behaviors we would generally consider morally reprehensible (Bandura, 2002). Dehumanization has been shown to lead to negative attitudes toward migrants (Kteily & Bruneau, 2017; Utych, 2018), racial minorities (Goff et al., 2008; Utych, 2020), women (Morris et al., 2018), and members of the other political party (Cassese, 2019; Martherus et al., 2021). At its most extreme, dehumanization has been used to justify genocide and mass atrocities (Dower, 1986).…”
Section: The Role Of Dehumanization In Evaluations Of Individualsmentioning
confidence: 99%
See 1 more Smart Citation
“…A final potential moderating effect of the dehumanization of masks is the race of the person wearing the mask. Dehumanization operates differently based on racial minority status -White Americans dehumanized Black players in the context of national anthem protests, but not White players (Utych, 2020b). Perceptions of mask wearing also vary based on race -Black individuals are perceived as more threatening when wearing homemade masks, but not surgical masks, than when they are not wearing masks, an effect that does not persist for White individuals (Christiani et al, 2020).…”
mentioning
confidence: 99%